Molecular investigation of the trinucleotide repeats within the Huntington disease gene in Southern Africa - September, Alison (Department of Medicine, 2024)
Huntington disease (HD) is an autosom 1 dominant, progressive neurodegenerative condition, which usually presents in mid-life. The disease-causing mutation was identified in 1993 and entails the expansion of an unstable repeat (CAG)n within exon 1 of the, HD gene (IT-15). A polymorphic (CCG)n repeat has been identified immediately 3' to the unstable disease-causing (CAG)n repeat, which is in linkage disequilibrium on HD chromosomes. This study was undertaken to investigate the polymorphic repeats; (CAG)n and (CCG)n within the HD gene, in a sub-group of HD patients and family members from a population where HD is infrequently observed. Primer pairs were used to amplify each trinucleotide repeat separately. Molecular investigations of 3 Southern African (SA) populations (SA indigenous black population, Mixed ancestry, and Caucasian populations) revealed that the (CAG)n repeat on the 300 non-HD associated chromosomes ranged from 11-37 repeats while repeats ranging from 38-101 were observed on the 106 HD-associated chromosomes analysed.